Analisis Efisiensi Sistem Kesehatan di Provinsi DKI Jakarta Tahun 2016-2018 - Siti Hilmiati Azyzia; Abyatar Fanuel Lantera; Andreas Billyarta Harsanico; Jessica Rahma Sekar Ayu; Muhammad Rizky Mardani (Journal of Economics and Business, 2020)
Every country certainly has a desire to improve the welfare of its people, as well as Indonesia. Indonesia is one of the developing countries that has not yet experienced good welfare, especially in health facilities. This is reflected in Jakarta, which is said to be the nation's capital, where there is still inequality in adequate health facilities. Community health is important because health is an index of well-being by looking at productivity and human quality. The purpose of this study is to see the efficiency of the Health system in Jakarta. The approach taken to see the efficiency of this health facility is the DEA (Data Envelopment Analysis) method by looking at the ratio of general practitioners to the puskesmas per 100,000 population, the ratio of nurses per 100,000 population, the ratio of general and special hospitals per 100,000 population and the ratio of puskesmas per 100,000 population. While the use of its output in the form of life expectancy. Based on the results of the analysis, North Jakarta was the only municipality that was efficient in its health system management during the observation year. In 2017-2018 there was one additional municipality that was efficient in its health system management, namely West Jakarta.